Short-Sales Constraints and the Diversification Puzzle - Reed, Adam V.; Saffi, Pedro A. C.; Van Wesep, Edward D. (Management Science, 2021)
Disagreement about stock valuation, combined with short-sales constraints, can increase asset prices. We build a model showing that, so long as investor beliefs are not perfectly correlated, investors disagree less about the value of a conglomerate than about each of its individual divisions. This generates a conglomerate discount with disagreement and short-sales constraints being complementary in explaining its cross-sectional variation. We test these predictions empirically and find substantial support: conglomerates have lower differences of opinion and lower short-sales constraints than pure-play firms. Furthermore, greater differences of opinion and tighter short-sales constraints are significant predictors of valuation differences between conglomerates and pure plays. This paper was accepted by Karl Diether, finance.